Growth convergence: some panel data evidence - Lee, M.; Longmire, R.; Mátyás, L.; Harris, Mark (ROUTLEDGE, 1998)
This paper implements a panel data approach of the Solow model to study the phenomenon of growth convergence for 22 OECD countries. It shows that although the derived estimable Solow model is probably underspecified from an econometric point of view, it is still possible to conclude that there is a likely convergence to a steady state rate of about 2-4%.